Aplikasi Metode Waiting Line Pada Pelayanan Antrian Pelanggan Jasa Ekspedisi - Bimo Setyo Wibowo; Agustian Suseno (Peneliti.net, 2022)
Technological developments have become faster in the industrial era 4.0. Various companies have experienced many changes, one of which is in the field of delivery services, namely PT. JNE. this makes the increase in the demand for goods delivery services to be greater which makes service queue problems. These problems have an impact on customer service which results in inconvenience for every customer. To solve this problem, the researcher applies the waiting line method which aims to find out the time needed to wait in service and queues. The results of the analysis of the application of the waiting line method are obtained waiting time in the queue is 9 minutes and the waiting time in service is 12 minutes so that the service queue is on display, therefore additional service facilities are needed